Probiotics Surface-Delivering Fiber2 Protein of Fowl Adenovirus 4 Stimulate Protective Immunity Against Hepatitis-Hydropericardium Syndrome in Chickens - Jia, Zhipeng; Pan, Xinghui; Zhi, Wenjing; Chen, Hang; Bai, Bingrong; Ma, Chunli; Ma, Dexing (Frontiers in Immunology, 2022)
Background and Objectives: Hepatitis-hydropericardium syndrome (HHS) caused by Fowl adenoviruses serotype 4 (FAdV-4) leads to severe economic losses to the poultry industry. Although various vaccines are available, vaccines that effectively stimulate intestinal mucosal immunity are still deficient. In the present study, novel probiotics that surface-delivering Fiber2 protein, the major virulence determiner and efficient immunogen for FAdV-4, were explored to prevent this fecal-oral transmitted virus, and the induced protective immunity was evaluated after oral immunization. Methods: The probiotic Enterococcus faeaclis strain MDXEF-1 and Lactococcus lactis NZ9000 were used as host strains to deliver surface-anchoring Fiber2 protein of FAdV-4. Then the constructed live recombinant bacteria were orally vaccinated thrice with chickens at intervals of two weeks. Following each immunization, immunoglobulin G (IgG) in sera, secretory immunoglobulin A (sIgA) in jejunum lavage, immune-related cytokines, and T cell proliferation were detected. Following challenge with the highly virulent FAdV-4, the protective effects of the probiotics surface-delivering Fiber2 protein were evaluated by verifying inflammatory factors, viral load, liver function, and survival rate. Results: The results demonstrated that probiotics surface-delivering Fiber2 protein stimulated humoral and intestinal mucosal immune responses in chickens, showing by high levels of sIgA and IgG antibodies, substantial rise in mRNA levels of cytokines, increased proliferative ability of T cells in peripheral blood, improved liver function, and reduced viral load in liver. Accordingly, the adequate protection against homologous challenges and a significant increase in the overall survival rate were observed. Notably, chickens orally immunized with E. faecalis/DCpep-Fiber2-CWA were completely protected from the FAdV-4 challenge, which is better than L. lactis/DCpep-Fiber2-CWA. Conclusion: The recombinant probiotics surface-expressing Fiber2 protein could evoke remarkable humoral and cellular immune responses, relieve injury and functionally damage of target organs. The current study indicates a promising method used for preventing FAdV-4 infection in chickens.